Women Language ‘Hidden Figure’ Movie Script Written By Allison Shroeder and Theodore Melfi - Yuniar Fatmasari; Rita Gustina (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2020)
Many factors can affect the way people communicate. One of them is gender. Compared to the men, women tend to use many language variations. Understanding the language variation used by women is important, so that its language function. In this research, the writers analyze the women's language features used by female characters in